A Putative Phosphatase, LSF1, Is Required for Normal Starch Turnover in Arabidopsis Leaves - Comparot-Moss, Sylviane (American Society of Plant Biologists, 2010)
A putative phosphatase, LSF1 (for LIKE SEX4; previously PTPKIS2), is closely related in sequence and structure to STARCH-EXCESS4 (SEX4), an enzyme necessary for the removal of phosphate groups from starch polymers during starch degradation in Arabidopsis (Arabidopsis thaliana) leaves at night. We show that LSF1 is also required for starch degradation: lsf1 mutants, like sex4 mutants, have substantially more starch in their leaves than wild-type plants throughout the diurnal cycle. LSF1 is chloroplastic and is located on the surface of starch granules. lsf1 and sex4 mutants show similar, extensive changes relative to wild-type plants in the expression of sugar-sensitive genes. However, although LSF1 and SEX4 are probably both involved in the early stages of starch degradation, we show that LSF1 neither catalyzes the same reaction as SEX4 nor mediates a sequential step in the pathway. Evidence includes the contents and metabolism of phosphorylated glucans in the single mutants. The sex4 mutant accumulates soluble phospho-oligosaccharides undetectable in wild-type plants and is deficient in a starch granule-dephosphorylating activity present in wild-type plants. The lsf1 mutant displays neither of these phenotypes. The phenotype of the lsf1/sex4 double mutant also differs from that of both single mutants in several respects. We discuss the possible role of the LSF1 protein in starch degradation.